Chemistry International : The News Magazine of IUPAC (De Gruyter, 1997)
Chemistry International is the newsmagazine of the International Union of Pure and Applied Chemistry (IUPAC). News about IUPAC, its chemists, its publications, its recommendations, its conferences and the work of its commissions and committees is published bimonthly in CI.